Ensino de oralidade em língua inglesa no novo ensino médio e a perspectiva do inglês como língua franca: uma análise da trilha de aprendizagem: TTT talk, talk tlks in english podcasting and vídeos creation - Ruaro, Milena (2024)
This qualitative research (Cohen; Manion; Morrison, 2004) deals with the teaching of orality in English in the New High School (NHS) from the perspective of English as a Lingua Franca (ELF). The general objective of the research is to develop a prototype in response to the Learning Trail entitled "TTT- Talk, Talk Talks in English - Podcasting & Videos Creation" focused on orality from the perspective of the ELF. As for the specific objectives, they seek to: i) investigate the Referential of the State of Paraná in articulation with the methodological guidelines of the Trail and ii) present a proposal for a prototype that meets the Trail. To compose the theoretical basis, in addition to the discussion of basic studies about ELF (Seidlhofer, 2011; Siqueira; Anjos, 2012; Gimenez et al, 2015, Calvo, 2013; El Kadri, 2013 ), a mapping of theses and dissertations was carried out on the CAPES portal regarding the teaching of orality in English, in order to ascertain the work already carried out in the area. These results still show few studies focused on orality in the new High School (NHS) and that are guided by the ELF perspective. From this framework, the study focused on the curricular component of the English language and the trail in the Paraná Framework. As main results, we identified the teaching methodologies and other strategies, in order to complement the National Common Curricular Base (BNCC) and together with digital literacy in the learning of English, through the TED Talk genre. As a way to meet the proposition of the Trail in focus, it is integrated in this work, the construction of a prototype elaborated from the Development Methodology Based on Educational Design (Filatro; Piconez, 2007); of studies on digital literacy in the classroom (Marzari, Leffa, 2013; Denardi; Marcos; Stankoski, 2021); in consonance with reflections on the TED Talk genre (Pletsch; Oliveira, 2021). The stages of this prototype, according to Filatro and Piconez (2007) are analysis, that is, it concerns the collection of data on the teaching of orality for the NEM, the verification of the Learning Trail, and readings about the TED Talk genre; design, refers to the construction of the prototype articulated to the implications of the ELF, activities with the main genre TED Talk, and the teacher's manual. In the development stage, we highlight the activities, for the 3rd year of NEM, that can provide the development of orality and the manual of this prototype directed to the teacher, in order to show the referrals with these activities. Thus, both the prototype and its manual seek to meet the perspective of the ELF, because the activities highlight the problematization with the pronunciation of English Speakers as a Mother Tongue (FILM); they address questions about varieties and accents, and encourage students' own production, valuing intelligibility.